2007
DOI: 10.1111/j.1570-7458.2007.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon impedes stalk penetration by the borer Eldana saccharina in sugarcane

Abstract: Many plants grown in soils amended with silicon (Si) display increased levels of resistance to attack by insect herbivores. This study aimed to determine if Si treatment impeded Eldana saccharina Walker (Lepidoptera: Pyralidae) stalk penetration and subsequent damage, as well as borer mass gain, on the node and internode of a susceptible (N11) and a resistant (N33) sugarcane cultivar. Sugarcane [Saccharum spp. (Poaceae)] cultivars were grown in a pot trial in Si‐deficient river sand, with (Si+) and without (Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 23 publications
4
72
2
3
Order By: Relevance
“…This higher accumulation of silicon is the reason for low borer damage in plots receiving higher doses of DAE. It has been hypothesized that "Si" deposited on the tissue surface acts as a physical barrier and it prevents physical penetration and / or makes the plant cells less susceptible to enzymatic degradation by insect pests (Salim and Saxena 1992) and (Kvedaras and Keeping, 2007). This mechanism is supported by the positive correlation between the Si content and the degree of suppression of insect pests which is well established through this investigation (Table 3).…”
Section: Silicon Content In Plant Samplesupporting
confidence: 72%
“…This higher accumulation of silicon is the reason for low borer damage in plots receiving higher doses of DAE. It has been hypothesized that "Si" deposited on the tissue surface acts as a physical barrier and it prevents physical penetration and / or makes the plant cells less susceptible to enzymatic degradation by insect pests (Salim and Saxena 1992) and (Kvedaras and Keeping, 2007). This mechanism is supported by the positive correlation between the Si content and the degree of suppression of insect pests which is well established through this investigation (Table 3).…”
Section: Silicon Content In Plant Samplesupporting
confidence: 72%
“…Some reports showed that N is essential for insects mainly for its role in amino acid production and protein synthesis (Sterner and Elser 2002;Schoonhoven et al 2005). On the other hand, many studies have shown that Si could enhance plant resistance to herbivores (Kvedaras and Keeping 2007;Reynolds et al 2009;Kvedaras et al 2010;Han et al 2015;Nikpay et al 2015). Furthermore, regression analysis in the present study clearly indicated that survival of BPH was correlated positively with plant tissue content of N, total free sugar (TFS), and SP but negatively with Si.…”
Section: Discussionsupporting
confidence: 61%
“…The results obtained in this study also strongly suggest a role for Si in the priming of JA-mediated inducible defense responses, in addition to the potential of Si to act as an insect antifeedant or as a component of physical barriers inhibitory to feeding (2,5,8). The analysis of JA-dependant defense-associated enzymes and genes (Figs.…”
Section: Discussionmentioning
confidence: 88%
“…An increased physical barrier produced by the deposition of Si beneath the leaf cuticles has long been considered to represent a major component underlying Si-mediated plant resistance to insect pests (5,8). Si deposition, occurring mainly as opaline phytoliths, is associated with increased rigidity and abrasiveness of plant tissues, thereby reducing their digestibility to herbivores.…”
mentioning
confidence: 99%